2021
DOI: 10.1111/ijfs.15289
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoencapsulation of Pogostemon cablin (Blanco) Benth. essential oil and its novel preservative effect for enhanced shelf life of stored Maize kernels during storage: Evaluation of its enhanced antifungal, antimycotoxin, antioxidant activities and possible mode of action

Abstract: The present evaluation aimed to synthesis and characterise the Pogostemon cablin essential oil encapsulated chitosan nanoemulsion (PCEO-CN) and evaluated its antifungal antimycotoxin and antioxidant activities. A total of twenty-six different chemical compounds were identified from P. cablin essential oil (PCEO), among which patchoulol (34.93%), α-bulnesene (17.76%) and α-guaiene (15.44%) were recorded as major components. The average size of PCEO-CN was 18.20 nm. The PCEO-CN showed concentration-dependent bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The use of gelatine (10%) and chitosan (1%) as spray coatings on vacuum-packed beef extends the shelf life to 21 days (Gedarawatte et al, 2021). Roshan et al (2022) showed that Pogostemon cablin essential oil encapsulated chitosan nanoemulsion (PCEO-CN) significantly protected maize seeds from mold-induced biodeterioration and aflatoxin B 1 biosynthesis for up to 30 days.…”
Section: Anthocyaninsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of gelatine (10%) and chitosan (1%) as spray coatings on vacuum-packed beef extends the shelf life to 21 days (Gedarawatte et al, 2021). Roshan et al (2022) showed that Pogostemon cablin essential oil encapsulated chitosan nanoemulsion (PCEO-CN) significantly protected maize seeds from mold-induced biodeterioration and aflatoxin B 1 biosynthesis for up to 30 days.…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Moreover, the ability of CSNPs to stabilize sensitive antioxidants, such as tea polyphenols and vitamins, can help reduce the lipid or protein oxidation of foods. Hence, nanostructured forms of chitosan can be considered as profitable value‐added products, which are used in a wide array of foods, packaging, encapsulation, biomedical remedy, and health promotion (Adebo et al, 2021; Gedarawatte et al, 2021; Roshan et al, 2022; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile EO of P. cablin is primarily constituted with sesquiterpenes, namely, patchoulene and patchouli alcohol (Sundaresan et al, 2012). Investigations on biological properties of the Pogostemon EO and phytochemicals revealed multidimensional pharmacological functions against a panel of targets (Hu et al, 2018;Roshan et al, 2022). Significant antifeedant activity of the EO has also been recorded against cosmopolitan pests (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Roshan et al . (2022) work provides ideas about synthesis and characterisation of the Pogostemon cablin essential oil nanoemulsion and its antifungal, antimycotoxin, and antioxidant activities for the enhancement of shelf‐life and nutritional attributes of maize, wherein the P . cablin essential oil nanoemulsion completely inhibited aflatoxin B 1 and fumonisin B 1 biosynthesis from toxigenic isolates of Aspergillus flavus and Fusarium verticillioides , respectively.…”
mentioning
confidence: 99%